2021
DOI: 10.1088/1361-6439/ac35c8
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and testing of microelectromechanical system spark gap switch based on streamer theory

Abstract: In order to realize that the fuze micro system has both high security and miniaturization characteristics, the spark gap research of Micro-Electro-Mechanical System safety system is carried out. So that to solve the safe and reliable function of the spark gap switch under the low power supply voltage (35 V) of the fuze micro system, the gas gap size and electrode radius are shown to significantly affect the gas breakdown voltage using streamer theory. Based on these results, a spark gap switch with triggering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies on mode 1 can be found in our previous work. In mode 2, which is more similar to trigger gas switches [14][15][16], the conduction current, delay, and jitter are important parameters that are used to evaluate device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on mode 1 can be found in our previous work. In mode 2, which is more similar to trigger gas switches [14][15][16], the conduction current, delay, and jitter are important parameters that are used to evaluate device performance.…”
Section: Introductionmentioning
confidence: 99%